Effects of nitrogen sources on the nitrate assimilation in Haloferax mediterranei: growth kinetics and transcriptomic analysis. Issue 2 (22nd November 2013) - Esclapez, Julia; Bravo‐Barrales, Gloria; Bautista, Vanesa; Pire, Carmen; Camacho, Mónica; Bonete, María J.
Abstract The haloarchaeon Haloferax mediterranei is able to grow in a defined culture media not only in the presence of inorganic nitrogen salt but also with amino acid as the sole nitrogen source. Assimilatory nitrate and nitrite reductases, respectively, catalyze the first and second reactions. The genes involved in this process are nasA, which encodes nitrate reductase and is found within the operon nasABC, and nasD, which encodes nitrite reductase. These genes are subjected to transcriptional regulation, being repressed in the presence of ammonium and induced with either nitrate or nitrite. This type of regulation has also been described when the amino acids are used as nitrogen source in the minimal media. Furthermore, it has been observed that the microorganism growth depends on nitrogen source, obtaining the lowest growth rate in the presence of nitrate and aspartate. In this paper, we present the results of a comparative study of microorganism growth and transcriptomic analysis of the operon nasABC and gene nasD in different nitrogen sources. The results are the first ever produced in relation to amino acids as nitrogen sources within the Halobacteriaceae family.